IMPLEMENTASI MANAJAMEN SEKOLAH DALAM MENYIAPKAN GURU KOMPETEN - Nurhayati Amanda Lubis (Sekolah Tinggi Agama Islam (STAI) Al-Ma'rif Buntok, 2025)
School management is one of the efforts to achieve school goals effectively and efficiently through planning, organizing, implementing, and supervising. The quality of learning is influenced by the competence possessed by a teacher. The purpose of this study is to determine the planning, organizing, implementing, and supervising of schools in preparing competent teachers. In this study, a qualitative approach was used with case study research, with data collection through interviews, observations, and documentation. Data analysis techniques by reducing, presenting, and concluding data. The results of this study are: 1) the planning carried out by schools in preparing competent teachers has been designed in such a way with various considerations. 2) organizing, namely determining the placement of teacher tasks. 3) providing space for teachers to hone their abilities and potential, and also providing supporting training to provide additional pedagogical knowledge for teachers. 4) supervision of teachers, namely by observing the results of the quality of learning during the learning process. It can be concluded that by implementing optimal school management, it will provide effective quality learning for students.